Hygroma Colli ; Sonographic Indication of Chromosomal Abnormality. a Case Report - Koerslo, Hamka; Zulmaeta, Zulmaeta (Indonesian Health Journal, 2025)
Hygroma colli is a congenital disorder in the form of cystic enlargement in the cervical region due to impaired development of the lymphatic system. This condition is often an indicator of chromosomal abnormalities, such as Turner syndrome and other aneuploidy. This case report aims to describe the process of identifying hygroma colli in a 17-week-old fetus through ultrasound examination and subsequent treatment. A 26-year-old primigravida woman was referred to the hospital for the discovery of a mass on the fetal neck through ultrasound. Follow-up examination showed the presence of symmetrical, thin, hypochic, unobstructed cystic masses in the lateral posterior region of the fetal neck with abnormalities of the pulmonary organs. Based on the findings, the pregnancy was decided to be terminated. These findings show the importance of prenatal ultrasound for early detection of hygroma colli and potential chromosomal abnormalities so that management can be planned more optimally.